Development of a Literacy and Numeration Learning Module Based on Local Wisdom, Project Based Learning, and TRI-N to Increase Student Independence - Arrahmi, Syukron Zahidi; Sukiyanto, Sukiyanto (Al-Khawarizmi, 2024)
Students' numeracy literacy abilities are still categorized as very low, this occurs due to a lack of teaching materials that are able to support increasing these abilities. One of the teaching materials that can support improving students' numeracy literacy skills is the use of literacy and numeracy modules. This development research aims to determine the feasibility of developing a numeracy literacy module based on local wisdom in Purworejo based on Project Based Learning and the teachings of Ki Hajar Dewantara Tri N (Niteni, Niroke, Nambahi) based on the assessment of experts and to determine the level of practicality of developing a numeracy literacy module applied in learning . This development research adopts the ADDIE model approach. Participants in this research were 29 students in class III at SDN Girigondo. The findings from this research indicate that (1) the module that has been developed has very high validity in accordance with the established criteria with an average of 3.9 on a Likeart scale based on assessments from three validators, namely material experts, media experts and language experts; (2) Students showed a positive response to the module developed with an acceptance rate of 97%, which indicates that the module meets the criteria very well in the learning context. Meanwhile, teacher responses to the module were also very positive with an acceptance rate of 100%, which confirms that this module is effective and suitable for use in the learning process.